(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This study highlights the ecological, economic, and aesthetic importance of selecting tree and shrub species for greening Karshi city. Drought- and salt-tolerant species, such as Elaeagnus angustifolia, demonstrate high efficiency in soil stabilization and dust retention. Decorative species like Rosa canina and Berberis vulgaris are recommended to enhance the aesthetic appeal of the urban landscape. These species contribute to improving public health by cleaning the air and optimizing the microclimate. The findings of this study can be instrumental in improving the ecological and social environment of Karshi city.